A possible complementary tool for diagnosing tuberculosis: a feasibility test of immunohistochemical markers - Seo, Kyung-Jin (Int J Clin Exp Pathol, 2015)
Differentiation of tuberculous granuloma (TG) from non-tuberculous granuloma (NG) is histopathologically difficult. We evaluated the usefulness of selected immunohistochemical markers to differentiate tuberculous granuloma (TG) and non-tuberculous granuloma (NG). We selected six biomarkers (FoxP3, TNF-beta, E-selectin [ESEL], indoleamine 2,3-dioxygenase [IDO], lactoferrin [LACT], and tartrate-resistant acid phosphatase [TRAP]) and immunohistochemically analyzed their expression in the presence of two types of granulomatous tissue samples, TG (n = 36) and NG (n = 31), using a microarray format. Three of those six biomarkers (LACT, IDO, and TNF-beta) were moderately accurate in discriminating TG from NG, individually and in combination, according to ROC analysis (AUC = 0.7-0.89, sensitivity = 55.6-77.8%, specificity = 71.0-100%). Our data indicate that selected immunohistochemical markers (LACT, IDO, and TNF-beta) can be used in ancillary tests to differentiate TG from NG in tissue samples. Further large-scale studies are required to validate our results.